Aβ40 has a subtle effect on Aβ42 protofibril formation, but to a lesser degree than Aβ42 concentration, in Aβ42/Aβ40 mixtures - Terrill-Usery, Shana E. (Arch Biochem Biophys, 2016)
Recent findings suggest that the senile plaques in Alzheimer’s disease may contain soluble amyloid-β peptide (Aβ) fibril precursors along with insoluble fibrils.. These soluble Aβ species, including oligomers and protofibrils, have been well-studied in vitro and are formed via non-covalent self-assembly of Aβ monomers. While both 40- and 42-residue forms of Aβ are observed in the human body, the majority of the Aβ aggregation work has been conducted on Aβ42 or Aβ40 separately, with relatively few investigations of mixtures. In order to study the effect of different combinations of Aβ40 and Aβ42 on protofibril formation, mixtures of either dry solid peptide, or purified Aβ40 and Aβ42 monomer solutions were mixed together and protofibril/monomer distributions were quantified. Increases in the Aβ42/Aβ40 ratio increased protofibril formation but the presence of Aβ40 in the mixed Aβ solutions had a significant negative impact on protofibril formation compared to equivalent solutions of pure Aβ42. Protofibril size was less affected, but β-sheet structure increased with protofibrils formed from higher Aβ42/Aβ40 ratio solutions. Direct measurement of Aβ42/Aβ40 ratios by C-terminal-selective ELISA found very little Aβ40 incorporated into protofibrils. The cumulative data emphasizes the critical importance of Aβ42, yet establishes Aβ40 as a regulator of Aβ42 aggregation.